PENGARUH PEMBERIAN DIMSUM AYAM KOMBINASI TEPUNG DAUN KELOR (MORINGA OLEIFERA) TERHADAP KADAR HAEMOGLOBIN REMAJA PUTRI - Oktavianis Oktavianis; Hafika Gusfiana (Maternal Child Health Care, 2023)
Anemia is one of major public health problems throughout the world, including Indonesia. One of the community groups with a high prevalence of anemia is adolescent girls. Anemia that often occurs in adolescent girls is iron deficiency anemia due to lack of nutrients that play a role in the process of forming hemoglobin. One food that is high in iron and protein is Moringa leaves. This study aimed to determine The Effect of Chicken Dimsum Combination of Moringa Leaf Flour (Moringa Oleifera) on hemoglobin Levels of Anemia in Young Women in Sijunjung Regency in 2022. The type of research was Quasi Experiment with pretest-posttest design with control group design. The population was adolescent girls in Sijunjung Regency. Consisting of 30 people in the intervention group and 30 people in the control group. The sampling technique was purposive sampling with inclusion and exclusion criteria. Primary data collection using Easy Touch GcHb was entered into the observation sheet. Data analysis with univariate and bivariate. The results showed that the average hemoglobin level in the pretest was 13.93 and the posttest was 14.37. The statistical test results obtained p = 0.000 (p <0.05), It means that there was an effect of chicken dimsum combination with Moringa leaf flour (Moringa Oleifera) on the hemoglobin levels of adolescent girls. In short, it can be concluded that there is an effect of chicken dimsum witth combination of Moringa leaf flour (Moringa Oleifera) on the hemoglobin levels of adolescent girls in Sijunjung Regency in 2022". Last, it is suggested that the health services do the collaboration with the schools to provide counseling on how to detect and prevent anemia, increase the intake of iron-rich foods such as Moringa leaves, and carry out routine hemoglobin checks.